Grit and Resilience as Predictors of Creativity Among Chinese English as a Foreign Language Teachers - Sun, Jia (Frontiers in Psychology, 2022)
Teachers have been viewed for many years as one of the most effective factors with an important role in academic and learning settings. Numerous studies have been carried out on teachers and their performances in the classroom. Feelings are one of the pillars of all humans which can have a crucial function in offering academia that can impact all domains of learning. The emotion of creativity is one of the subcategories of feelings that is worthy to people and the community. Nonetheless, as a significant mental attribute, it has not been attended to enough by experts in language teaching until now. The other factors that seem concerning creativity are grit and resilience. It has been determined that grit has a basic function in the educational and teaching cycle because gritty educators are more inspired to handle difficulties in hard situations. Moreover, to beware of these difficulties as a response to unprecedented situations, a similar intellectual concept rises in positive psychology known as resilience, which explains the persistence and highlights individuals’ skills. Therefore, the present study delineates the relationship of these notions with language teachers’ creativity. To this end, 264 male and female Chinese EFL teachers took part in the present study, and their creativity, grit, and resilience were scrutinized by filling out the related questionnaires. The obtained data were analyzed using multiple regression and correlation analyses. The results of the multiple regression showed that both grit and resilience could significantly predict creativity although grit is a better predictor of creativity. Some educational implications of the research about the outcomes of the research under academic circumstances are suggested.